2005
DOI: 10.1098/rspb.2005.3231
|View full text |Cite|
|
Sign up to set email alerts
|

An invasive lineage of sculpins,Cottussp. (Pisces, Teleostei) in the Rhine with new habitat adaptations has originated from hybridization between old phylogeographic groups

Abstract: Fish abundance surveys in the Rhine system have shown in the past two decades that there is a rapid upriver invasion of a freshwater sculpin of the genus Cottus. These fish are found in habitats that are atypical for the known species Cottus gobio, which is confined to small cold streams within the Rhine drainage. Phylogeographic analysis based on mitochondrial haplotypes and diagnostic single nucleotide polymorphisms indicates that the invasive sculpins are hybrids between two old lineages from the River Sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
222
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(232 citation statements)
references
References 21 publications
9
222
1
Order By: Relevance
“…A total of 20 weirs were identified (Figure 1) and, although data on their ages were not available, landowners and Environment Agency records confirmed that weirs have been present in the River Rye catchment for at least 200 years. Since the generation time of bullheads is $1-2 years (Nolte et al 2005), this represents $100-200 bullhead generations. It is therefore reasonable to assume that weirs represent a potentially relevant influence on both long-and short-term gene flow.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 20 weirs were identified (Figure 1) and, although data on their ages were not available, landowners and Environment Agency records confirmed that weirs have been present in the River Rye catchment for at least 200 years. Since the generation time of bullheads is $1-2 years (Nolte et al 2005), this represents $100-200 bullhead generations. It is therefore reasonable to assume that weirs represent a potentially relevant influence on both long-and short-term gene flow.…”
Section: Methodsmentioning
confidence: 99%
“…Ellstrand 1992;Rhymer & Simberloff 1996;Taylor et al 2006). Finally, hybridization may facilitate the origin of new species with new adaptations arising through a recombination of existing genes (Schliewen & Klee 2004;Nolte et al 2005) and may even facilitate bursts of adaptive radiation from hybrid swarms (Seehausen 2004). Theoretical considerations suggest that the evolutionary consequences of interspecific hybridization depend on the adaptive landscape experienced by the hybridizing populations (Buerkle et al 2003;Seehausen et al 2008).…”
Section: Introduction Part I: Hybridization and Mating Preferencesmentioning
confidence: 99%
“…Here, success depends on the fixation of favourable new gene combinations from the two species [48]. For example, there are suggestions that new hybrid gene combinations facilitated critical ecological changes in several recently proposed hybrid species, including sculpins [49], Rhagoletis flies [50], and butterflies [51,52*]. In these cases, species of hybrid origin have colonized novel habitats, most likely through the expression of transgressive traits.…”
Section: Evolutionary Consequences Of Introgression and Hybrid Speciamentioning
confidence: 99%